KEBIASAAN MAKANAN IKAN TILAN (Mastacembelus erythrotaenia, Bleeker 1850) DI SUNGAI MUSI [Food habit of fire eel, Mastacembelus erythrotaenia Bleeker 1850 in Musi River] - Syarifah Nurdawati; Wahyu Yuliani (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2009)
Tilan, Mastacembelus erythrotaenia is one of an economic fish that the population has been degradated. The research was aiming to describe the information of food habits of tilan fish in Musi River. The sampling was conducted every month from December 2007 to Juli 2008 and samples were collected by using pancing (hook and line), sondong (electro fishing), Jaring kantong (trammel net), rawai (long line) and belat (seine net). A total of 1001 fish was caught. The stomach content was analyzed based on index of preponderance method. Based on this analysis, the main food was Sesarma eydouxi. According to this research, Mastacembelus erythrotaenia was the selective crustacivorous predator, that main food was similar in every month and station. This information be used for management resources of Mastacembelus erythrotaenia, aquaculture, and conservation.